Persistence of inflammatory and vascular mediators 5 months after hospitalization with COVID-19 infection - Melhorn, James; Alamoudi, Asma; Mentzer, Alexander J.; Fraser, Emily; Fries, Anastasia; Cassar, Mark Philip; Kwok, Andrew; Knight, Julian Charles; Raman, Betty; Talbot, Nick P; Petousi, Nayia (Frontiers in Medicine, 2023)
ABSTRACT Background and Aim: In acute severe COVID-19, patients present with lung inflammation and vascular injury, accompanied by an exaggerated cytokine response. In this study, our aim was to describe the inflammatory and vascular mediator profiles in patients who were previously hospitalised with COVID-19 pneumonitis, months after their recovery, and compare them with those in patients recovering from severe sepsis and in healthy controls. Methods: 27 different cytokine, chemokine, vascular endothelial injury and angiogenic mediators were measured in the plasma of forty-nine patients 5.0±1.9 (mean±SD) months after they were hospitalised with COVID-19 pneumonia, eleven patients 5.4±2.9 months after hospitalisation with acute severe sepsis, and eighteen healthy controls. Results: Compared with healthy controls, IL-6, TNFα, SAA, CRP, Tie-2, Flt1 and PIGF were significantly increased in the post-COVID group, and IL-7 and bFGF were significantly reduced. While IL-6, PIGF and CRP were also significantly elevated in post-Sepsis patients compared to controls, the observed differences in TNFα, IL-7, Tie-2, Flt-1 and bFGF were unique to the post-COVID group. TNFα levels significantly correlated with the severity of acute COVID-19 illness (spearman’s r=0.30, p<0.05). Furthermore, in post-COVID patients, IL-6 and CRP were each strongly negatively correlated with gas transfer factor %predicted (spearman’s r=-0.51 and r=-0.57, respectively, p<0.001) and positively correlated with CT abnormality scores at recovery (r=0.28 and r=0.46, p<0.05, respectively). Conclusion: A unique inflammatory and vascular endothelial damage mediator signature is found in plasma months following acute COVID-19 infection. Further research is required to determine its pathophysiological and clinical significance.